Solutions of systems of nonlinear functional-differential equations bounded in the entire real axis and their properties - Pelyukh, G. P.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
For a system of nonlinear functional-differential equations with a linearly transformed argument, we establish the existence and uniqueness conditions for a solution bounded in the entire real axis and study the properties of this solution.